The Relationship of Mother's Anxiety Level and Husband's Support With IUD Selection in Binanga Health Center - Melia Shintia Mutiara Pohan; Yoana Manurung; Ica Fauziah Harahap; Riska Yanti Harahap; Yeni Zahara Harahap (International Journal of Public Health Excellence (IJPHE), 2022)
Husbands have an important role, where husbands are highly demanded not only as breadwinners but husbands as motivators in various policies that will be decided, including family planning. Therefore, a husband who supports his wife using long-term contraceptives such as the IUD can be an incentive for a woman to participate in government programs. The researcher's preliminary study at the Binanga Health Center, Barumun Tengah District, on 15 (fifteen) people, who used 4 pills, 7 injections, 2 condoms, 2 IUDs and no MOW and MOP. This study aims to determine the relationship between maternal anxiety levels and husband's support with the choice of intrauterine device (IUD). This research uses total sampling research . The sample in this study were couples of childbearing age (EFA) as many as 30 respondents. The results showed that the level of anxiety was severe (46.7%), moderate (30%) and mild (23.3%). Meanwhile, husbands who do not support (53.3%), are less supportive (23.3%) and support (23.3%). And who chose the IUD (30%) and Non IUD (70%). The conclusion of the study showed that there was a relationship between the level of maternal anxiety and husband's support with the choice of an intrauterine device (IUD).